DJ1 expression downregulates in neuroblastoma cells (SK-N-MC) chronically exposed to HIV-1 and cocaine - Roy, Upal; Atluri, Venkata S. R.; Agudelo, Marisela; Yndart, Adriana; Huang, Zaohua; Nair, Madhavan (Frontiers in Microbiology, 2015)
Background: HIV-associated neurological disorder (HAND) has long been recognized as a consequence of Human Immunodeficiency Virus (HIV) infection in the brain. The pathology of HAND gets more complicated with the recreational drug use such as cocaine. Recent studies have suggested multiple genetic influences involved in the pathology of addiction and HAND but only a fraction of the entire genetic risk has been investigated so far. In this regard, role of DJ1 protein (a gene linked to autosomal recessive early-onset Parkinson’s disease) in regulating dopamine transmission and reactive oxygen species (ROS) production in neuronal cells will be worth investigating in HIV-1 and cocaine exposed microenvironment. Being a very abundant protein in the brain, DJ1 could serve as a potential marker for early detection of HIV-1 and/or cocaine related neurological disorder. Methods: In vitro analysis was done to observe the effect of HIV-1 and/or cocaine on DJ1 protein expression in neuroblastoma cells (SK-N-MC). Gene expression and protein analysis of DJ1 was done on the HIV infected and/or cocaine treated SK-N-MC and compared to untreated cells using real time PCR, Western Blot and flow cytometry. Results: Gene expression and protein analysis indicated that there was a significant decrease in DJ1 expression in SK-N-MC chronically exposed to HIV-1 and/or cocaine. Conclusion: This is the first study to establish that DJ1 expression level in the neuronal cells significantly decreased in presence of HIV-1and/or cocaine indicating oxidative stress level of dopamine neurons.